Smartphone dan Pemaknaannya Di Kalangan Kaum Muda Karawang: (Studi Kritis Atas Subjektivitas Pengguna Smartphone) - Arindawati, Weni Adityasning (Jurnal Ilmu Komunikasi AKRAB, 2019)
ABSTRACTThe digital age allows anyone to easily access the internet through a smartphoneat any time and place. Young people who consider the phase are still in the process ofcharacter formation, relatively open to changes from the outside tend to be dynamic.The conception of young people who are active, dynamic and sensitive to changes in thisstudy above discussion of young people who use smartphones not only supportscommunication, but also helps other things that can be interpreted in accordance withcultural cooperation that produces new cultural meaning. This study aims to gain anunderstanding of the meaning of smartphones for its users, namely young people inKarawang. This study uses consideration of technological determination that emphasizesthe aspect of subjectivity as smartphone users on the meaning of the communicationtools they mean in their lives.Keywords: Smartphone, Cultural Meaning, Determinism Technology, McLuhan